The Effect of Processing and Cooling Methods on Coleus tuberosus in vitro Starch Digestibility - Jhauharotul Muchlisyiyah; Tri Dewanti Widyaningsih; Retno Wulansari; Hera Sisca Prasmita (agriTECH, 2021)
Coleus tuberosus, also known as black potato, is one of the Indonesian local tubers consumed as a carbohydrate substituent. Therefore, this study aimed to examine the effect of processing and cooling methods on the in vitro digestibility of black potato starch. Furthermore, two factors Randomized Block Design with a 2x3 experimental design was used, which consisted of processing methods (boiling, roasting, and microwave) and cooling at room temperature and 4 °C for 24 hours with 3 repetitions. Black potato flour was compared with the raw form, by assessing some parameters, namely Resistant Starch (RS), Slowly Digestible Starch (SDS), Rapidly Digestible Starch (RDS), and Glycemic Index (GI). Also, the analysis of total starch, moisture, and color was performed, hence raw black potatoes generally have 10% resistant starch (%wb). Different treatments of cooking and cooling had a significant effect (α = 0.05) on moisture content, total starch, RS, RDS, SDS, GI, brightness (L), and yellowness (b). Black potatoes subjected to the processing method followed by cooling had lower RDS and increased RS content. Furthermore, refrigeration at 4°C for 24 hours reduced the digestibility of black potato starch more than cooling at room temperature. Contrarily, microwaved black potato cooled at room temperature showed a higher digestion rate compared to the raw counterpart. Conclusively, processing followed by cooling reduces the GI and increases the RS content of Coleus tuberosus.